2014
DOI: 10.1177/0022343314537860
|View full text |Cite
|
Sign up to set email alerts
|

Freedom of foreign movement, economic opportunities abroad, and protest in non-democratic regimes

Abstract: Allowing or restricting foreign movement is a crucial policy choice for leaders. We argue that freedom of foreign movement reduces the level of civil unrest under non-democratic regimes, but only in some circumstances. Our argument relies on the trade-offs inherent in exit and voice as distinct strategies for dealing with a corrupt and oppressive state. By permitting exit and thereby lowering its relative costs, authoritarians can make protest and other modes of expressing dissatisfaction less attractive for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…This finding is relevant to several literatures. First, research on the international determinants of protests is only starting to pay attention to emigration and financial remittances (Barry et al 2014;Miller and Ritter 2014;Escribà-Folch, Meseguer, and Wright 2018;Germano 2018). In the literature on protests, resources are deemed essential for grievances to be transformed into collective action.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is relevant to several literatures. First, research on the international determinants of protests is only starting to pay attention to emigration and financial remittances (Barry et al 2014;Miller and Ritter 2014;Escribà-Folch, Meseguer, and Wright 2018;Germano 2018). In the literature on protests, resources are deemed essential for grievances to be transformed into collective action.…”
Section: Discussionmentioning
confidence: 99%
“…Weinberg and Bakker (2015) investigated the relationship between food prices inside a country and social unrest, reporting a positive relationship between them. Barry et al (2014), who use a cross-national sample of 125 countries from 1981 to 2007, find that freedom of foreign movement and the existence of economic opportunities abroad reduce civil unrest. Kibria et al (2020) using a sample of 34 countries in Sub Saharan Africa (SSA) between 1972 and 2013 found that an increase in foreign direct investment reduces the risk of civil violence for skilled-labor intensive fuel-resource rich SSA countries.…”
Section: Civil Unrest In Financial Marketsmentioning
confidence: 99%
“…However, there is little research on this and less so in autocratic contexts. Dionne, Inman, and Montinola (2014) show that remittance receivers are more likely to protest in Africa, whereas Barry et al (2014) argue that open emigration policies reduce protest in nondemocracies by allowing dissenters to leave. Yet open emigration policies may increase protest if migrant remittances decline when economies weaken in destination countries.…”
Section: Remittances and Political Behaviormentioning
confidence: 99%